The mitochondrial genome analysis of Flavoperla hatakeyamae (Plecoptera: Perlidae) - Hao, Caihao (Mitochondrial DNA B Resour, 2020)
In this study, we analyzed the entire mitochondrial genome of Flavoperla hatakeyamae, which has 15,730 bp in length. This complete mitochondrial genome possessed 13 protein coding genes (PCGs), 2 ribosomal RNA genes, 22 transfer RNA genes, and 1 control region. The nucleotide composition of the complete sequence of mitochondrial genome was accounting for 35.0%, T for 31.3%, C for 21.2%, G for 12.5%, and A + T for 66.3%. Among the 13 protein-coding genes, the starting codon of 12 protein-coding genes was ATN except the starting codon of COII was ACC. In addition, 11 of the protein-coding genes used conservative termination codon TAA/TAG, except for COII and ND5 which terminated by a single T. Based on Bayesian (BI) and maximum-likelihood (ML) methods, we found that the genus Flavoperla and Niponiella were gathered into one branch and the species of Perlinae were clustered in one clade.